Loads for the design of the industrial building frame - T.V. Zolina; P.N. Sadchikov (Inzhenerno-stroitelʹnyĭ zhurnal, 2020)
The article considers the issues of assessing the reliability of structures of an industrial building equipped with bridge cranes. The implementation of the research concept is based on a probabilistic approach as the most appropriate to the random nature of technogenic and extreme impacts. A mathematical model is constructed that takes into account the random nature of the formation and perception of the framework structure of the totality of loads. To substantiate the method, an extensive amount of statistical data was generated on the loads of bridge cranes of various types and meteorological information on wind and snow for individual climatic regions of Russia. The stationary probabilistic models for crane and quasistationary models for snow and wind loads are substantiated. The proposed algorithms for their implementation are adapted for the automation of calculations using the software developed by the authors of the article “DINCIB-new”. Numerical calculations of the operability of the frame structures of the operated buildings of production shops under the action of a combination of loads. A comparative analysis of the obtained results with the normative allowed us to conclude that it is necessary to include when forming combinations of loads that affect the change in the stress-strain state of the frame structures of an industrial building, lateral forces. As a result of experimental and theoretical studies, refinements were made to the previously proposed calculation schemes and calculation methods, allowing to design the supporting structures of the frames in accordance with the actual conditions of their actual work.